Overcoming the Limitations of Transient Photovoltage Measurements for Studying Recombination in Organic Solar Cells. Issue 5 (20th March 2020) - Azzouzi, Mohammed; Calado, Philip; Telford, Andrew M.; Eisner, Flurin; Hou, Xueyan; Kirchartz, Thomas; Barnes, Piers R. F.; Nelson, Jenny
Abstract : Transient photovoltage (TPV) measurements are frequently used to study recombination processes in thin‐film solar cells by probing the decay of a small optically induced voltage perturbation to infer the charge carrier dynamics of devices at open circuit. However, the validity of this method to probe organic semiconductors has recently come into doubt due to large discrepancies in the reported carrier lifetime values for the same systems and the reporting of unrealistic reaction order values. Herein, the validity of TPV to extract reliable charge carrier lifetimes in thin‐film solar cells is explored through the use of time‐dependent drift‐diffusion simulations and measurements. It is found that in low‐mobility materials, TPV serves primarily as a probe of charge carrier redistribution in the bulk rather than bulk recombination dynamics and that the extracted time constant is highly mobility dependent. To address this shortcoming, transient photocharge, a new technique to measure the charge carrier density during photovoltage decay, is introduced and applied to study the recombination dynamics in a series of (fullerene and nonfullerene) organic solar cell systems. It is shown that using this technique the charge carrier recombination lifetime in the active layer is more accurately determined. Abstract : Transient photovoltage (TPV) mostly probes the dynamics of charge carriers close to the transport‐layer interfaces. These dynamics are affected by other properties of the device such as the charge‐carrier mobility. A different optoelectronic technique that can reliably measure the lifetime of charge carriers is developed. By applying both techniques to a series of devices, the TPV lifetime is found to be misleading.